Prediction Of Amount Of Use Of Planning Family Contraception Equipment Using Monte Carlo Method (Case Study In Linggo Sari Baganti District) - Rani Yunima Astia; Julius Santony; Sumijan Sumijan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
Family planning aims to minimize birth rates in Indonesia. To conduct socialization, it is carried out to existing fertile couples. Pus is a married couple whose wife is in the range of 15-49 years. Contraception itself consists of 2 periods, namely short and long. Where the pus can choose according to what they want, therefore there is often a lack of stock. Thus it is necessary to predict how many contraceptives are used with a method to be more efficient. The Monte Carlo method is used which is a numerical analysis method that involves a sample of random numbers. Where to use the previous year's data to get the predicted results of the next year in the form of numbers. After passing the simulation series the percentage results have been obtained with an average of over 80%.